Fenomena Kesenian Gedrug Dalam Kehidupan Masyarakat Desa Limbangan Kecamatan Limbangan Kabupaten Kendal Jawa Tengah - Anggun Ida Mawadda (Institut Seni Indonesia Yogyakarta, 2026)
Gedrug Art Phenomena from Limbangan Village Community in Limbangan Sub-district, Kendal District, Central Java. This is about “Gedrug Art Phenomena from Limbangan Village Community in Limbangan Sub-district, Kendal District, Central Java” the purpose is to know, review, and describe the phenomenon of interest in Limbangan Village, Limbangan Sub-district, Kendal District towards Gedrug Arts. To explore the problems in this study, using analytical descriptive method with anthropological approach, and study of the coreography of the text and context. Gedrug Arts or knows as Rampak Gedrug Buta Dance or Rampak Buta Dance is a popular genre of traditional dance performing arts in the form of the group. Gedrug Arts composition coming from Magelang, Central Java was introduced in Limbangan Village by Sulasno, one of the residents of Limbangan Village. Sulasno was the initiator of the formation of this Association Paguyuban Rampak Candra Budaya. Society of Limbangan Village have an opinion that Gedrug Arts has its own charm. The presence of Gedrug Arts is something new for the people of Limbangan Village in Kendal District. The art that presents the motion of the gedrug bumi, property of masks, klinthing, and typical properties becomes the main magnet that’s why people to join in. Art that is synonymous with an energetic and dynamic pattern of movement would be a new taste for the people of Limbangan Village. Only about 2 years have passed, but the enthusiasm from the society is so clear. Judging from the number of audience who came, it was also seen from the frequent performances of Gedrug Art compared to traditional arts called Jatilan which were precisely the identity of the Limbangan Village community has less audience. Gedrug Arts is expected to be able to preserve an art. Although the art isn’t original art that has taken root in this village. As much as any group or art community, it should not be competitions. But it becomes a means to move forward together in preserving national culture.Keywords : phenomenon, kesenian Gedrug, Desa Limbangan Kendal